Ethnozoological Study of Native Birds and Mammals Associated to Fruit Orchards of Zacualpan de Amilpas, Morelos, México - García-Flores, Alejandro (2017)
This research is an ethnozoologic study based on the analysis of the traditional knowledge that the autochthonous inhabitants of the community of Zacualpan de Amilpas, Morelos, Mexico, have in what refers to the native birds and mammals associated with groves. The methodology was applied in four stages: contact with the pertinent authorities, identification of key informants, grove survey, interviewing and sampling to observe and corroborate the species identified by the informants. Thus, 34 bird common names pertaining to 26 species, 6 orders and 15 families were registered. Passeriformes was the order with the highest species number, and Tyrannidae and Icteridae were the most representative families. For mammals, 16 common names were recognized pertaining to 18 species, 6 orders and 10 families; the order Carnivora and the family Mephitidae had the largest species number. The use values registered were: alimentary, medicinal, ornamental and as good-luck charms. Species are hunted using shotguns and slingshots. Community members recognize three environmental services (seed dispersion, insect predation and pollination) that 16 species carry out. We conclude that the reassessment of local traditional knowledge is important for the use, management and conservation of birds and mammals associated with traditional groves.